Robust gait recognition: a comprehensive survey. Issue 1 (31st October 2018) - Rida, Imad; Almaadeed, Noor; Almaadeed, Somaya
Abstract : Gait recognition has emerged as an attractive biometric technology for the identification of people by analysing the way they walk. However, one of the main challenges of the technology is to address the effects of inherent various intra‐class variations caused by covariate factors such as clothing, carrying conditions, and view angle that adversely affect the recognition performance. The main aim of this survey is to provide a comprehensive overview of existing robust gait recognition methods. This is intended to provide researchers with state of the art approaches in order to help advance the research topic through an understanding of basic taxonomies, comparisons, and summaries of the state‐of‐the‐art performances on several widely used gait recognition datasets.